PENGARUH PROSES REKRUTMEN TERHADAP KINERJA KARYAWAN PADA PT FEDERAL INTERNATIONAL FINANCE (FIF) DI KOTA SAMARINDA - Rahmi Azaria Dani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
The purpose of this study was to examine and determine the effect of the recruitment process simultaneously and partially on employee performance at PT. Federal International Finance (FIF), and to test and find out which variable has the most significant effect on employee performance. Data analysis tools used are validity test, reliability test, classic assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, F test, T test, and dominant test. The results showed that the method and source of recruitment simultaneously had a significant effect on employee performance. This is evidenced by the value of sig. Fcount = 0.018 <Alpha 0.05. In the t test results (partial) the recruitment source partially has a significant effect on employee performance. This is evidenced by the value of sig. tcount X2 X2 0.005> 0.05, where the most influential is the source of recruitment with the results of standardized coefficients beta of 0.465. From the results of the study it was shown that the method and source of recruitment had a significant effect on performance by 15.2%, while the remaining 84.8% was determined by other variables not included in the study. The suggestion from researchers for PT Federal International Finance (FIF) in Samarinda City is expected to further improve employee recruitment standards and processes in the recruitment of company employees to provide quality human resources.